Upaya Perusahan Pembiayaan Non Bank Dalam Mengembangkan Usaha Mikro, Kecil dan Menengah : (Studi Deskriptif Pemberian dan Pengembalian Kredit Oleh Pt "X") - Syahrizal, Iman; Machdum, Sari Viciawati (Jurnal Ilmu Kesejahteraan Sosial, 2016)
Entrepreneurship basically is not an easy matter. Despite of the challenges, organizations of both government and non-governmental organizations have developed entrepreneurial development activities. As a non-governmental organization, profit-oriented PT “X” also plays a role in the process of entrepreneurship development by undertaking financing activities to micro enterprises. This article describes the efforts of PT “X” as a Non-Bank Company that implements the implementation of credit loan and return in UMKM. Based on qualitative research, the research result showed that PT “X” as a company has potential because it can give positive contribution to the development of UMKM in Indonesia. However, in its implementation, PT “X” still used a minimalist approach. The micro and capital goods financing activities that have been partially and have not been integrated continuously in rolling out micro credit financing program for UMKM. It coused many contradictions between the financing that is carried out by the company with community assistance efforts that should be done in the process of developing UMKM.